2019
DOI: 10.1002/jbio.201900002
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cerebral blood flow and hemodynamic parameters during acute hyperglycemia in mice model observed by dual‐wavelength speckle imaging

Abstract: In this study, we use dual-wavelength optical imaging-based laser speckle technique to assess cerebral blood flow and metabolic parameters in a mouse model of acute hyperglycemia (high blood glucose). The effect of acute glucose levels on physiological processes has been extensively described in multiple organ systems such as retina, kidney, and others. We postulated that hyperglycemia also alters brain function, which in turn can be monitored optically using dual-wavelength laser speckle imaging (DW-LSI) plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Adults with obesity are at increased risk of cerebrovascular disease and neurological impairment. Acute and chronic hyperglycaemia impairs systemic vascular function (Piconi et al 2004;Ceriello et al 2008;Shemesh et al 2019) and contributes to development of vascular disease (Ceriello et al 2008;Habas & Shang, 2018). We hypothesized that ketone supplementation would confer benefit on the cerebrovasculature via the direct effects of β-OHB on cerebral metabolism and CBF (Hasselbalch et al 1996;Mikkelsen et al 2015;Svart et al 2018), as well as indirectly through its glucose-lowering effects (Neptune, 1956;Myette-Côté et al 2018Walsh et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Adults with obesity are at increased risk of cerebrovascular disease and neurological impairment. Acute and chronic hyperglycaemia impairs systemic vascular function (Piconi et al 2004;Ceriello et al 2008;Shemesh et al 2019) and contributes to development of vascular disease (Ceriello et al 2008;Habas & Shang, 2018). We hypothesized that ketone supplementation would confer benefit on the cerebrovasculature via the direct effects of β-OHB on cerebral metabolism and CBF (Hasselbalch et al 1996;Mikkelsen et al 2015;Svart et al 2018), as well as indirectly through its glucose-lowering effects (Neptune, 1956;Myette-Côté et al 2018Walsh et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The brain relies on the continuous supply of glucose as its main source of energy and metabolism, and changes in blood glucose concentrations directly affect brain function. Previous studies have shown that acute or chronic hyperglycemia is accompanied by reduced CBF ( Shemesh et al, 2019 ). The regional cerebral cortex is hypoperfused in T2DM patients, and chronic hyperglycemia disrupts the blood–brain barrier, leading to permanent brain cell damage, which demonstrates that altered cerebral hemodynamics is a potential mechanism of cognitive decline in T2DM patients ( Jansen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, we exploratory investigated the role of glucose ingestion and acute hyperglycaemia on the response of cerebral haemoglobin to sprint exercise. Although the brain almost exclusively relies on glucose for its metabolism and brain’s glucose uptake increases during exercise, hyperglycaemia has been shown to decrease the cerebral metabolic rate of oxygen (Ishibashi et al, 2016; Shemesh et al, 2019) and brain connectivity (Ishibashi et al, 2018) in healthy young participants. Acute and chronic hyperglycaemia also decreases CBF (Duckrow et al, 1985; Shemesh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although the brain almost exclusively relies on glucose for its metabolism and brain’s glucose uptake increases during exercise, hyperglycaemia has been shown to decrease the cerebral metabolic rate of oxygen (Ishibashi et al, 2016; Shemesh et al, 2019) and brain connectivity (Ishibashi et al, 2018) in healthy young participants. Acute and chronic hyperglycaemia also decreases CBF (Duckrow et al, 1985; Shemesh et al, 2019). In our experiment, glucose ingestion did not alter O 2 Hb and HHb responses to the repeated sprints exercise, although improving performance.…”
Section: Discussionmentioning
confidence: 99%